Faktor-Faktor Pemilihan LPK Yasa Luhur Salatiga dan Implikasi Manajerial Berdasarkan Six Market Model - Theodorus Christopher Widihandojo; Sentot Suciarto Athanasius (Universitas Katolik Soegijapranata, Semarang, 2022)
The purpose of this research was to see what factors drive students to choose LPK Yasa Luhur Salatiga, and how to survive in the competition using six market model. The instrument used to find these factors was questionnaire provided, that were distributed to the students of Yasa Luhur. Analysis of the data was done using the Factor Exploratory Analysis. The results of the research showed that there were six factors. The market also sees that the teachers who work at Yasa Luhur were very competent in their field. Facilities and rewards given to Yasa Luhur also played an important role, which attracted the students to firmly decide that they were gaining their higher education at Yasa Luhur.